Stimulasi Magnetik Lebih Meningkatkan Kemampuan Fungsional pada Pasien Nyeri Punggung Bawah Dibanding Stimulasi Elektris - Aditya Johan Romadhon; Heru Purbo Kuntono; M. Mudatsir Syatibi (Poltekkes Kemenkes Surakarta, 2020)
Background: A long with the development of physical agents modalities, there are many recent modalities that has many beneficial for physical therapy practice, generally physical agents modalities are suit for musculoskeletal cases, one of beneficial effect for musculoskeletal case is maintaining of muscle’s physiology, electrical stimulations are familiar modalities that usually find in physiotherapy practice, these modalities are use to inhibit pain signal and produce muscle contraction. Recently a new physical agent modality such as magnetic stimulation also has smiliar effect such as electrical stimulations, however there are less evidence to compare magnetic and electrical stimulation for musculoskeletal problems. Objective: Purpose of this study is to compare magnetic and electrical stimulation effect to reduce pain and improve functional activity in low back pain patients. Methods: Random of 60 low back pain patients were recruited, devided into two groups, Group 1 given magnetic stimulation and Group 2 given electrical stimulation, after four mounth intervention two days in every weeks, pain index and functional activity measured with Oswestry instrument, inclusion criteria for subjects was pain symptom less than 1 year, 25-65 years old, there’s no neurologic deficit, married and cooperative to be subject. Exclusion criteria of subject was lumbo-sacral fracture condition, pregnancy, subject with heart disease, osteophorosis, or systemic disease. Data analyzed by dependent and independent t test. Results: based on the result by using independent t test, we have p value 0.001, it means there’s significant different between two groups. After 4 mounth intervention we find reducing pain index and improvement of functional activity in two groups, Group 1 the Oswestry score is 0.2 ± 0.08, while Group 2 the Oswestry score is 0.3 ± 0.05. Conclussion: magnetic stimulation is more effective to reduce pain index and improve functional activity by using Oswestry instrument than electrical stimulation.